Tata Uji Beban Aksial Model Fondasi Tiang Bor Pendek di Lapangan Untuk Studi Tahanan Dukung Ujung - Nugraha, Andrias Suhendra (Universitas Kristen Maranatha, 2003)
Axial load testing on short drilled pile foundation models in the field requires several criteria to be met, including: depth of the tip support layer, adjustments to the capacity and arrangement of the test equipment so that it can still refer to the testing standards. In order for the axial working load on the foundation model to be carried only by the toe bearing resistance, the frictional resistance of the blanket is eliminated through lubrication with liquid silicone. The toe bearing resistance is mobilized at large deformations from 18%d to 30%d. The load test tip bearing resistance value is only about half of the empirically calculated tip bearing resistance.